Licensing of Natural Areas Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-150, a 2-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use herbicides to natural areas in Florida. Published by the UF Pesticide Information Office, February 2007.